The BERA guide to mental health and wellbeing in schools : exploring frontline support in educational research and practice - Jayman, Michelle; Glazzard, Jonathan; Rose, Anthea; Quickfall, Aimee (Emerald Publishing Limited, 2024)
Positioning wellbeing at the heart of a well-functioning school community, this timely guide brings the debate on the escalating child and adolescent mental health crisis to a broad audience. A research-informed yet accessible introduction to both the scholarly discourse and real-world cases of mental health in education, The BERA Guide to Mental Health and Wellbeing in Schools focuses on the UK while providing messages and practical tips for an international readership. Chapters examine policy approaches and the pivotal role schools have acquired within the government's settings-based approach to mental health. The first section presents the theoretical framework and policy context, and the second is dedicated to a selection of case studies from schools in the UK, drawing attention to current issues encountered in education, showcasing exemplars of good practice and sharing innovative approaches to tackling poor mental wellbeing. Published in partnership between the British Educational Research Association (BERA) and Emerald Publishing, The BERA Guides are short, research-informed yet accessible introductions to key, interdisciplinary topics impacting education research and practice for a broad academic audience.
Includes index.
Keywords: School children -- Mental health.; School children -- Mental health services.; Education -- Educational Psychology.; Educational psychology.; elektronické knihy; electronic books